ANALYSIS OF PHTHALATE PLASTICIZER IN JORDANIAN BOTTLED WATERS BY LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROPHOTOMETRY (LC-MS/MS) - Al Khatib, Ahed J; Habib, Ishaq Y; Muhammad, Murtala; Danladi, Fahad I; Bala, Sani S; Adamu, Auwal (European Scientific Journal, ESJ, 2014)
A promising method for the quantitative determination of phthalate esters was optimized in nine different Jordanian commercial bottled water samples using liquid chromatography tandem -mass spectrometry (LCMS/ MS). The present study described an efficient method for the determination of this compound using LC-MS/MS as the analysis technique. The compound was separated with C18 Thermo fisher gold column (100mm x 5μm) through a flow rate of 1ml/min using isocratic mobile phase). The method was validated using triplicate analyses, recovery experiment and statistical analysis. Liquid- liquid extraction was employed as a preconcentration step with methanol as the extraction solvent and methanol: ammonium acetate: de-ionized water: formic acid (68%:30%:2%:0.1%) as the mobile phase. The molecular ion was found to be m/z 390.56 and the base peak was found to be m/z 149. The correlation coefficient (R2) was found to be 0.9996. The LOD and LOQ were found to be 0.02ng/ml and 0.06 ng/ml respectively. This method showed satisfactory recovery of 98.08%, CV of 0.960%, SD of 0.006, error of 0.929 and 95% CI of 0.960 + 0.007 . The ranges of the calculated concentrations of the commercial mineral bottled waters were found to be from 0.729-1.26ng/ml.